2016
DOI: 10.1177/1479972316680844
|View full text |Cite
|
Sign up to set email alerts
|

Effect of respiratory rehabilitation techniques on the autonomic function in patients with chronic obstructive pulmonary disease: A systematic review

Abstract: Patients with chronic obstructive pulmonary disease (COPD) show several extrapulmonary abnormalities such as impairment in the autonomic function (AF). Similarly, the use of respiratory training techniques such as controlled breathing techniques, noninvasive mechanical ventilation (NIMV), and oxygen supplementation for AF modulation in patients with COPD is popular in existing literature. However, the evidence to support their use is nonexistent. A systematic search of studies reporting on the effect of contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 42 publications
0
11
0
4
Order By: Relevance
“…Based on technique the basis of breathing used, pranayama can be divided into Dirgha Pranayama (deep and slow regular breathing techniques), Sukha Pranayama (practical breathing techniques to create a steady breathing rhythm), Sukha Purvaka Pranayama, and Vyaghrah Pranayama (tiger breathing technique). 16 Some main things that must be considered before doing any type of pranayama, which is ensuring that the doer is in a comfortable position, relax, upright body, and minimal distraction. Pranayama then can be begun by breathing in through the nose, holding the breath, and exhaling through the mouth periodically.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on technique the basis of breathing used, pranayama can be divided into Dirgha Pranayama (deep and slow regular breathing techniques), Sukha Pranayama (practical breathing techniques to create a steady breathing rhythm), Sukha Purvaka Pranayama, and Vyaghrah Pranayama (tiger breathing technique). 16 Some main things that must be considered before doing any type of pranayama, which is ensuring that the doer is in a comfortable position, relax, upright body, and minimal distraction. Pranayama then can be begun by breathing in through the nose, holding the breath, and exhaling through the mouth periodically.…”
Section: Resultsmentioning
confidence: 99%
“…Yoga helps improve physical performance, and increases range of motion in COPD patients through improved skeletal muscle strength, flexibility, endurance, coordination, and static and dynamic stability. 16 The decrease in the tendency of dyspnea to occur due to decreased reactivity of the sympathetic nerves in prayanama yoga practitioners. This is based on the presence of bronchial dilation which improves the abnormal breathing pattern and reduces the tension of the inspiratory and expiratory muscles.…”
Section: Resultsmentioning
confidence: 99%
“…our study was conducted in the context of existing data on the impact of physical rehabilitation on the condition of CoPd patients; it turns out to play a significant role in the treatment and prevention of the disease. Many works are devoted to the use of physiotherapy treatment in addition to drug therapy [9,10,15,19,20]. in our opinion, to improve the quality of life of CoPd patients, it is necessary to employ daily kinesiotherapy, whose main means is breathing exercises, in combination with nebulizer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…in our opinion, to improve the quality of life of CoPd patients, it is necessary to employ daily kinesiotherapy, whose main means is breathing exercises, in combination with nebulizer therapy. Many studies have shown the positive effect of respiratory gymnastics [10,14,17,19] and physical training [1,3,9] on the indicators of external respiration function, namely the increase in forced expiratory volume in 1 second. The results of several randomized controlled studies have revealed that the use of manual therapy with physical training helps to improve physical performance [5,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation